Pendekatan Target Heart Rate untuk Kenyamanan Berolahraga dalam Meningkatkan Imunitas Tubuh pada Masa Pandemi Covid-19 - Utama, Anak Agung Gede Eka Septian; Widnyana, M; Pramana, I Putu Yudi (TIN: Terapan Informatika Nusantara, 2020)
Covid-19 has shocked the world and even WHO calls this outbreak a global pandemic. In order to prevent the spread and victims, the government issued a work from home policy so that all activities at home are at risk with sedentary activities. Exercise is an effort to reduce sedentary activity, reduce boredom, maintain health and even increase the immune system. However, what kind of exercise is right and good to do during a pandemic in order to avoid viruses and stay comfortable exercising. Therefore, this study aims to look at the Target Heart Rate Approach for Exercise Comfort in Increasing Immunity during the Covid-19 Pandemic. This research method uses a literature study with a descriptive analysis approach